HUKUM PERTANAHAN DAN EKSISTENSI MANUSIA - Sinjar, Arafah (AKTUALITA, 2011)
The history of agrarian law in Indonesia prior to the independence day werefeudalistic and capitalistic where the society felt shackled and lack of freedom in theownership, had no authority to manage the land and farmland optimally. Landreform through Law Number 5 Year 1960 pertinent to Agrarian Principles (BAL) isone of the efforts aimed at holding the division of land in order to set a better controland ownership leveling as well as guaranteed by law, it was the first time of theintroduction of the concept related to the rights which held by the government andgive the authority of the land to the government but the not the owenership of theland. The purpose of this concept is to achieve prosperity for people and gain socialjust and prosperous.Keywords: Agrarian law, land reform, Islamic law.